A Modified Iterative Approach for Fixed Point Problem in Hadamard Spaces - Asifa Tassaddiq; Wakeel Ahmed; Shahid Zaman; Asma Raza; Usman Islam; Kwara Nantomah (Journal of Function Spaces)
The role of iterative algorithms is vital in exploring the diverse domains of science and has proven to be a powerful tool for solving complex computational problems in the most trending branches of computer science. Taking motivation from this fact, we develop and apply a modified four-step iterative algorithm to solve the fixed point problem in the Hadamard spaces using a total asymptotic nonexpansive mapping. MATLAB R2018b is used for numerical experiments to ensure a better convergence rate of the proposed iterative algorithm with existing results.